2011
DOI: 10.1039/c1ob06285a
|View full text |Cite
|
Sign up to set email alerts
|

Origins of the diastereoselectivity in hydrogen bonding directed Diels–Alder reactions of chiral dienes with achiral dienophiles: a computational study

Abstract: In this study, the origins of diastereoselectivity in the hydrogen bonding assisted Diels-Alder reactions of chiral dienes with achiral dienophiles have been investigated with density functional methods. The distortion/interaction model has been applied to shed light on the origins of selectivity. C9-Substituted chiral anthracene templates (R = (CH(3))(OCH(3))(H), R = (CH(3))(OH)(H), R = (CH(3))(CH(2)CH(3))(H) and R = (-CH(2)-C(CH(3))(OCH(3))(H)) are used to rationalize the role of a stereogenic center and H-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 85 publications
0
10
0
Order By: Relevance
“…Conveniently, there is no special computer code required to perform activation strain analyses: all necessary quantities can be computed using any of the regular quantum‐chemical software packages available. As a result, the activation strain model has been applied by various research groups, on a range of chemical processes, such as nucleophilic substitution, cycloaddition, oxidative addition, isomerization, and many other processes from organic and organometallic chemistry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conveniently, there is no special computer code required to perform activation strain analyses: all necessary quantities can be computed using any of the regular quantum‐chemical software packages available. As a result, the activation strain model has been applied by various research groups, on a range of chemical processes, such as nucleophilic substitution, cycloaddition, oxidative addition, isomerization, and many other processes from organic and organometallic chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…9 Conveniently, there is no special computer code required to perform activation strain analyses: all necessary quantities can be computed using any of the regular quantum-chemical software packages available. As a result, the activation strain model has been applied by various research groups, on a range of chemical processes, such as nucleophilic substitution, 1,[10][11][12][13][14][15][16][17][18][19] cycloaddition, [20][21][22][23][24][25][26][27][28][29][30][31][32][33] oxidative addition, [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] isomerization, [50][51][52][53][54][55] and many other processes from organic…”
Section: Introductionmentioning
confidence: 99%
“…A critical feature of the DA reactions studied here is the presence of hydrogen bond interactions in both the RC and TS structures (Figures and S4). Such intermolecular hydrogen bonds have been suggested to be the origin of the diastereoselectivity in reactions involving chiral dienes, and this topic has already been assessed using computational chemistry . Therefore, we shall not focus on the role of hydrogen bonding in the studied DA reactions, but rather on the reactivity trends and electronic properties that characterize such cycloadditions.…”
Section: Resultsmentioning
confidence: 99%
“…There are some studies on H‐bonding–induced diastereoselectivity in different reactions . Kilic et al reported that diastereoselectivity can be obtained through H‐bonding in some aziridination reactions .…”
Section: Introductionmentioning
confidence: 99%
“…Kilic et al reported that diastereoselectivity can be obtained through H‐bonding in some aziridination reactions . On the other hand, according to Jones et al and Aviyente et al diastereoselective [4 + 2] cycloadditions can also be performed guided by H‐bonding. One study reported that internally H‐bonded chiral methylene nitrones undergo diastereoselective [3 + 2] cycloaddition .…”
Section: Introductionmentioning
confidence: 99%